Bile acids drive chemotaxis of Clonorchis sinensis juveniles to the bile duct. - Shunyu Li; Won Gi Yoo; Jin-Ho Song; Tae Im Kim; Sung-Jong Hong (PLoS Neglected Tropical Diseases, 2018)
Clonorchiasis is a neglected tropical disease caused by Chinese liver fluke, Clonorchis sinensis infection. C. sinensis is a biological carcinogen causing cholangiocarcinoma in humans. In the mammalian host, C. sinensis newly excysted juveniles (CsNEJs) migrate from the duodenum into the bile duct. Bile drives the chemotactic behavior of CsNEJs. Little is known about which components of bile induce the chemotaxis. We designed a chemotaxis assay panel and measured the chemotactic behavior of CsNEJs in response to bile or bile acids. The CsNEJs migrated toward 0.1-1% bile but away from 5-10% bile. The CsNEJs showed strong chemoattraction to cholic acid ≥25 mM, but chemorepulsion to lithocholic acid ≥0.25 mM. To the CsNEJs, mixture of cholic acid and lithocholic acid was chemoattractive at a ratio greater than 25:1 but chemorepulsive at one smaller than that. Regarding migration in the mammalian hosts, high concentration of lithocholic acid in the gallbladder bile may repel CsNEJs from entering it. However, bile in the hepatic bile duct has a chemoattractive strength of cholic acid but a trace amount of lithocholic acid. Collectively, our results explain why the CsNEJs migrate principally to the hepatic bile ducts, bypassing the gallbladder.